THE IMPACT OF ZEROING METHOD TO VIETNAM’S TRADE IN THE PROVISION OF THE WTO - Muhammad Anas; M. Putra Iqbal (Jurnal Ilmiah Mahasiswa Bidang Hukum Kenegaraan, 2020)
Abstract - Anti-Dumping agreements allow governments to adopt “anti-dumping” actions. As the method of protection to the local industries, anti-dumping duties are thus imposed on the exporting country which has been accused of dumping goods in importer country.  However, these provisions are often misused by countries to get more profit from their production, one of which is the zeroing method as the example on United States – Antidumping Measures on Certain Shrimp from Vietnam. Zeroing under the WTO is important to research because there are still lack of definition and understanding among the members about this topic. There is a significant possibility that WTO members could use the zeroing to calculate dumping margin and it can harm the exporters. This research uses normative legal research that provide systematic exposition of the rules governing a particular legal category, analyses the relationship between rules and explain areas of difficulty of the Agreement on Implementation of Article 6 of GATT 1994.Keywords: Anti-Dumping, Dumping, GATT 1994, Zeroing, WTO.